Political Emancipation and the ‘Ticklish Subject’: Dilemmas of the Lacanian Left - Morgan, David (Sociologija. Mintis ir veiksmas, 2017)
The purpose of this paper is to tentatively explore the plausibility of the application of aspects of Lacanian psychoanalytic theory (and practice) to the purposes of Leftist political discourse. We live in an era when the forces of conservative political reaction are increasingly coming to the fore across Western democracies. In many Western states the reactionary right is in the ascendency: while the Left seems largely mired in political disarray and introspective impotence. Might the theories and insights of Jacques Lacan offer the Left some hope of a revivified intellectual and ideological cogency? This paper will attempt to draw together themes and ideas arising from recent scholarship within the field of Lacanian studies so as to explore ways in which the psychoanalytic theory and practice of Lacan might be utilised in the service of contemporary Leftist politics. In particular recent Lacanian scholarship has suggested that the provocative and fertile work of the scholar Slavoj Žižek might provide the foundation for just such a Lacanian Leftist renaissance. Contrary to this, this paper suggests that psychoanalysis itself should perhaps be regarded as a fundamentally tragic mode of thought – which might thus be intrinsically unsuited to the emancipatory purposes of the Left. Instead the paper will suggest that Lacanian theory might best serve the Left on a tactical level: as a radical interpretative technique whereby the texts and discourses of bourgeois cultural hegemony may be subjected to revivified critical scrutiny.